Practical Fundamentals of Clinical MEG Interpretation in Epilepsy - Laohathai, Christopher; Ebersole, John S.; Mosher, John C.; Bagić, Anto I.; Sumida, Ai; Von Allmen, Gretchen; Funke, Michael E. (Frontiers in Neurology, 2021)
Magnetoencephalography (MEG) is a neurophysiologic test that offers a functional localization of epileptic sources in patients considered for epilepsy surgery. The understanding of clinical MEG concepts, and the interpretation of these clinical studies, are very involving processes that demand both clinical and procedural expertise. One of the major obstacles in acquiring necessary proficiency is the scarcity of fundamental clinical literature. To fill this knowledge gap, this review aims to: 1) explain the basic practical concepts of clinical MEG relevant to epilepsy with an emphasis on single equivalent dipole (sECD), which is one the most clinically validated and ubiquitously used source localization method, 2) illustrate and explain the regional topology and source dynamics relevant for clinical interpretation of MEG-EEG in the respective clinical contexts, and 3) provide a structured and organized approach to the interpretation of overall MEG-EEG results focused on magnetic source images (MSI).